The Influence Of Institutional Ownership, Managerial Ownership, And Company Size On The Integrity Of Financial Reports - Santika, Sindi; Kurniawan, Elan (Summa : Journal of Accounting and Tax, 2023)
This study aims to determine the effect of Financial Statement Integrity on Institutional Ownership, Managerial Ownership, and Company Size in Mining Sector Companies Listed on the IDX for the 2018-2021 Period. The population of this study includes all mining companies listed on the IDX for the 2018-2021 period. The sample was taken using the purposive sampling method. The independent variable in this study is Institutional Ownership which is measured by dividing the number of shares owned by the institution by the number of shares outstanding, Managerial ownership is measured by dividing the number of shares owned by Management by the number of shares outstanding, and Size The company is measured by multiplying Ln by the number of assets. The dependent variable in this study is the Integrity of Financial Statements as measured by the Accounting Conservatism method. The results of this study indicate that: (1) Institutional Ownership has a negative effect on the Integrity of Financial Statements. (2) Managerial ownership has no effect on the Integrity of Financial Statements. (3) Company size has a positive effect on the integrity of financial statements.